Elevated serum substance P level as a predictive marker for moderately emetogenic chemotherapy‐induced nausea and vomiting: A prospective cohort study. (27th December 2020) - Park, Hyung Soon; Won, Hye Sung; An, Ho Jung; Cho, Sung Shim; Kim, Hyun Ho; Sun, Der Sheng; Ko, Yoon Ho; Shim, Byoung Yong
Abstract: Chemotherapy‐induced nausea and vomiting (CINV) is an unbearable side effect. Identifying high emetic risk patients and providing more active antiemetics strategies are mandatory to improve the tolerability of chemotherapy. In this prospective cohort study, leptin, ghrelin, and substance P were measured at baseline, day 3, and day 14 during the first cycle of chemotherapy. Nausea and vomiting were measured each day for the first 4 days of the first cycle of chemotherapy. Eighty‐two patients were enrolled. Colorectal cancer (61%) and gastric cancer (35.4%) were common cancer types. All patients received moderate emetic risk chemotherapy. Forty‐five (54.9%) patients had nausea, and 15 (18.3%) patients experienced vomiting. In univariate analysis, a higher level of baseline substance P, which is a target of NK1‐RA (Neurokinin 1 receptor antagonist), was a significant predictive marker for chemotherapy‐induced nausea [odds ratio (OR): 2.6, 95% confidence interval (CI): 1.02–6.62, p  = 0.046]. Regarding chemotherapy‐induced vomiting, patients with higher levels of substance P had a greater chance of vomiting [OR: 1.72, 95% CI: 0.49–5.99, p  = 0.395] than those with lower levels of substance P. In patients receiving moderate emetic risk chemotherapy, active antiemetics, including NK1‐RA, could be considered for those with high levels of substance P. Abstract : For patients with elevated substance P level, NK1‐RA (NK1 receptor antagonist, aprepitant) could be used, although these patients receive moderate emetic risk chemotherapy. This could improve the quality of life of patients receiving chemotherapy, and chemotherapy without dose reduction might have chance to improve treatment outcome for these patients.